Integrating Peer Tutoring and Behavioristic-Structuralism for Effective Shorof Instruction in Higher Education - Faruq, Ahmad Umar; Aslihah, Indy; Fuad, Muhammad Sabitul; Husna, Miftahul (Didaktika Religia, 2025)
This study aims to analyze the implementation of the behavioristic–structuralist approach through the peer tutoring method in teaching Arabic morphology (maharah shorof) to students of the Arabic Language Education Department at UIN Syekh Wasil Kediri. The research was motivated by students’ low mastery of Arabic morphological patterns due to teacher-centered traditional learning methods. Using a mixed-methods approach with an Explanatory Sequential Design, quantitative data were collected through pre-test and post-test, followed by qualitative data from classroom observations and interviews. The participants consisted of 19 undergraduate students (Class C) and graduate students as tutors. Findings revealed an increase in students’ mean scores from 77.11 to 85.79, with a p-value of 0.0079 (<0.05), indicating a statistically significant improvement. Qualitative findings showed that the integration of behavioristic reinforcement and structuralist analysis through peer tutoring encouraged more active, collaborative, and analytical learning behaviors. The study concludes that the behavioristic–structuralist approach effectively enhances Arabic morphology learning outcomes by combining behavioral conditioning and systemic linguistic understanding.